Правова характеристика принципів діяльності Національної поліції Україні та проблеми їх дотримання в сфері забезпечення публічної безпеки і порядку в умовах воєнного стану - Казанчук, І. Д.; Kazanchuk, I. D.; Казанчук Ірина Дмитрівна (Актуальні питання у сучасній науці. - 2023. - № 3(9). - С. 319-331, 2023)
Проаналізовано зміни і доповнення, які несені до Закону України «Про Національну поліцію» та інших нормативно-правових актів, і на підставі яких були розширені повноваження поліції в умовах введення в Україні правового режиму воєнного стану. Приділено окрему увагу особливостям дотримання та реалізації основних принципів поліцейської діяльності в сфері забезпечення публічної безпеки і порядку. Наголошено, що чітке правове визначення принципів поліцейської діяльності сприятиме глибшому розумінню їх змісту, належному правозастосуванню та зміцненню законності в діяльності поліції. Вказано, що подальше удосконалення правових засад реалізації принципів діяльності Національної поліції в умовах воєнного стану дозволить пришвидшити процес формування статусу Національної поліції як правоохоронного органу європейського зразка, який ефективно виконує головне завдання – надання поліцейських послуг населенню.

The article analyzes scientific doctrines regarding the definition of the concept of "principle", outlines its content and significance for law enforcement from the point of view of administrative and legal science. The actual definition of the principles of the National Police of Ukraine is provided, which should be understood as a set of fundamental, guiding ideas that are embedded in the content of the police as a state authority that carries out the law enforcement function of the state, and on the basis of which certain rules of behavior of police officers are formed during the performance of their official duties powers, implementation of legally established tasks and functions. The legal description of the principles listed in the Law of Ukraine "On the National Police" and by which the police should be guided in their activities is given, namely: 1) rule of law; 2) observance of human rights and freedoms; 3) legality; 4) openness and transparency; 5) political neutrality; 6) interaction with the population on the basis of partnership; 7) continuity. It is indicated that it is especially important to adhere to the specified principles when police officers ensure public safety and order, because they correspond to constitutional and international prescriptions. The article analyzes the changes and additions made to the Law of Ukraine "On the National Police" and other normative legal acts, and on the basis of which the powers of the police were expanded in the conditions of the introduction of the legal regime of martial law in Ukraine. With this in mind, special attention was paid to the peculiarities of observing and implementing the main principles of police activity in the field of ensuring public safety and order. The author concluded that a clear legal definition of the principles of police activity will contribute to a deeper understanding of their content, proper law enforcement and strengthening of legality in police activity. It is also indicated that the further improvement of the legal basis for the implementation of the principles of the National Police in the conditions of martial law will allow to speed up the process of forming the status of the National Police as a law enforcement body of the European model, which effectively fulfills the main task of providing police services to the population.

Проанализированы изменения и дополнения, внесенные в Закон Украины «О Национальной полиции» и других нормативно-правовых актов, на основании которых были расширены полномочия полиции в условиях введения в Украине правового режима военного положения. Уделено особое внимание особенностям соблюдения и реализации основных принципов полицейской деятельности в сфере обеспечения публичной безопасности и порядка. Указано, что дальнейшее усовершенствование правовых основ реализации принципов деятельности Национальной полиции в условиях военного положения позволит ускорить процесс формирования статуса Национальной полиции как правоохранительного органа европейского образца, эффективно выполняющего главную задачу – предоставление полицейских услуг населению.
Legal characteristics of the principles of the National Police of Ukraine and the problems of their observance in the sphere of ensuring public safety and order under the conditions of the state of martial
Keywords: Національна поліція України; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; принципи поліцейської діяльності; principles of police activity; принципы полицейской деятельности; воєнний стан; martial law; военное положение; забезпечення публічної безпеки і порядку; ensuring public safety and order; обеспечение публичной безопасности и порядка; правові засади; legal basics; правовые основы; Україна; Ukraine; Украина